Penyuluhan Gizi Online dengan Media Video Audio Visual “Tetap Fit Saat Puasa dan Pasca Puasa dengan Gizi Seimbang” - Norhasanah Norhasanah; Yuliana Salman (Jurnal Abdimas Kesehatan (JAK), 2021)
Ramadan fasting is a mandatory fast that Muslims do during the month of Ramadan. Diet during Ramadan tends to change, due to differences in meal times compared to other months. In order to maintain good health during fasting and post-fasting, we still need to pay attention to the application of balanced nutrition. The target audience of this activity is 97 students, the Recording and Health Information Study Program of STIKes Husada Borneo. The expected output of this activity is the goal of obtaining information about the application of balanced nutrition during fasting and post-fasting, so as to improve attitudes that may be lacking, thus the behavior will be better. The media of this activity is online counseling using audio-visual video. Activities carried out in stages including confirmation of activities, attendance, pre test, opening, delivery of material, post test, and closing. The results showed that the category of good knowledge as much as 21% before counseling increased to 42% after counseling, and the category of less knowledge as much as 48% before counseling decreased to 27% after counseling. Similar activities can be continued to other target audiences either with the same media that can be carried out online so that they can still be carried out during a pandemic where maintaining distance still needs to be considered related to "social distancing".